Mathematical methods in the social science, 1959 - Arrow, Kenneth J.; Karlin, Samuel; Suppes, Patrick (Stanford Stanford university press, 1960)
USA. Compilation of conference papers presented at a meeting to study applications of mathematics research methods in the social sciences - covers economics and economic theory, scientific management, theoretical and psychological aspects of learning, etc. Bibliographys.
Keywords: Economics mathematical models; Psychology mathematical models; Social sciences mathematics